Essentials of OCT in ocular disease - Agarwal, Amar; Kumar, Dhivya Ashok (Thieme Medical Publishers, Inc, 2015)
Written by the leading authorities in the field, Essentials of OCT in Ocular Disease is a core clinical reference on this important new technology used to examine the structure of the eye. It provides residents and practicing ophthalmologists with essential information on how to use OCT in various clinical scenarios and guidance on patient management. Chapters include coverage of recent innovative diagnostic applications as well as OCT-guided surgical procedures,including IOL position, DMEK, PDEK, GLUED IOL, and subtenon injection